Export Performance and Geography in Croatia - Artuc, Erhan; Iootty, Mariana; Pirlea, Ana Florina (World Bank Group, Washington, DC, 2014)
This paper uses the gravity model to analyze whether the varying export performance of Croatian counties can be explained by their proximity to border gates, ports, and other county-specific characteristics. The analysis finds that longer distances to border gates increase trade frictions significantly for many product categories, although these frictions have been decreasing between 2007 and 2012. The paper analyzes the county specific factors that are associated with variation in export performance, net of distance. Results show that exports are strongly and positively correlated with motorway and road density, the size of the labor force, low-skill ratio, and the number of patents. These variables are also associated with a greater diversity of exports in terms of products and destinations. Several general policy implications are highlighted. The significant association between motorway and road density and export volume, number of destinations, as well as the diversity of exported products may indicate that improvements in connectivity and facilitation of transport could still play a significant role in enhancing regional trade outcomes. Similarly, good performance in research and development may significantly help to spur competitiveness and allow local producers to enter new markets in products and destinations, which in turn can increase the level of diversification and boost resilience to global economic shocks.